Two ResD-Controlled Promoters Regulate ctaA Expression in Bacillus subtilis - Paul, Salbi (American Society for Microbiology, 2001)
The Bacillus subtilis ResDE two-component system plays a positive role in global regulation of genes involved in aerobic and anaerobic respiration. ctaA is one of the several genes involved in aerobic respiration that requires ResD for in vivo expression. The ctaAB-divergent promoter regulatory region has three ResD binding sites; A1, A2, and A3. The A2 site is essential for in vivo promoter activity, while binding sites A2 and A3 are required for full ctaA promoter activity. In this study, we demonstrate the role of ResD∼P in the activation of the ctaA promoter using an in vitro transcription system. The results indicate that the ctaA promoter (binding sites A2 and A3) has two transcriptional start sites. Binding site A2 was sufficient for weak transcription of the upstream promoter (Pv) by Eς(A), transcription which was enhanced approximately 1.5-fold by ResD and 5-fold by ResD∼P. The downstream promoter (Ps) required both binding sites A2 and A3 and was not transcribed by Eς(A) with or without ResD∼P. RNA polymerase (RNAP) isolated from B. subtilis when cells were at the end of exponential growth (T(0)) or 3, 4, or 5 h into the stationary phase (T(3), T(4), or T( 5), respectively) was used in in vitro transcription assays. Maximal transcription from Ps required T(4) RNAP plus ResD∼P. RNAP isolated from a spo0A or a sigE mutant strain was not capable of Ps transcription. Comparison of the Ps promoter sequence with the SigE binding consensus suggests that the ctaA Ps promoter may be a SigE promoter. The collective data from ResD footprinting, in vivo promoter deletion analysis, and in vitro transcription assays suggest that ctaA is transcribed during late exponential to early stationary phases of growth from the Pv promoter, which requires ResD binding site A2, Eς(A), and ResD∼P, and during later stationary phase from Ps, which requires binding sites A2 and A3, ResD∼P, and Eς(E) or a sigma factor whose transcription is dependent on SigE.